Wear-resistant and corrosion-resistant metal part and surface treatment process thereof
Through a specific surface treatment process, metal parts with excellent wear and corrosion resistance are prepared and retained, which solves the problem of gloss loss caused by improved wear and corrosion resistance in the prior art.
Patent Information
- Application Number
- CN202411714723.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-27
AI Technical Summary
While the existing metal parts surface treatment process improves wear and corrosion resistance, it often leads to the loss of the metal surface gloss, affecting appearance and functionality.
Through specific process steps and material selection, metal parts with excellent wear and corrosion resistance are prepared. The process design enables the metal surface to form a protective layer with a higher contact angle, reducing the contact area of corrosive media, while maintaining the gloss of the metal surface. Specific steps include forming a hydrophobic coating of micro-nano composite structure using fluoroalkyl modified thiol POSS and ethanol, and treating and spin-coating the coating B by oxygen plasma to enhance the mechanical locking and wear resistance of the coating.
It realizes that the surface of metal parts has excellent wear and corrosion resistance, and can retain the original luster, taking into account both function and beauty.
Smart Images

Figure BDA0005156644980000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface treatment technology, in particular to a wear-resistant and corrosion-resistant metal part and a surface treatment technology thereof. Background Art
[0002] In modern industrial production, metal parts are widely used in various types of machinery, equipment and building structures due to their high strength and good electrical and thermal conductivity. However, metal materials are often affected by wear and corrosion in actual use, resulting in performance degradation and shortened service life. Especially in some harsh environments, such as marine, chemical and mining fields, the wear and corrosion problems of metal parts are particularly prominent. Therefore, the development of metal parts with excellent wear resistance and corrosion resistance has become the focus of industry development.
[0003] Traditional metal surface treatment processes, such as electroplating and spraying, can improve the wear and corrosion resistance of metal parts to a certain extent, but often lead to the loss of metal surface gloss, affecting the appearance and functionality. With the increasing demand for high-performance metal parts, there is an urgent need for a surface treatment technology that can improve the wear and corrosion resistance of metals while retaining the original gloss of metal parts.
[0004] The present invention provides a wear-resistant and corrosion-resistant metal part and a surface treatment process thereof. Through specific process steps and material selection, the prepared metal part has excellent wear resistance and corrosion resistance. At the same time, the process design forms a protective layer with a high contact angle on the metal surface, which can not only effectively reduce the contact area of the corrosive medium, but also maintain the gloss of the metal part surface, thereby achieving a balance between function and aesthetics. Summary of the invention
[0005] The object of the present invention is to provide a wear-resistant and corrosion-resistant metal part and a surface treatment process thereof to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A surface treatment process for wear-resistant and corrosion-resistant metal parts, comprising the following steps: S1: adding ferric chloride to methanol, stirring evenly, adding concentrated hydrochloric acid, petroleum ether, and toluene in sequence, stirring evenly, adding the stirred mixture to a petroleum ether solution of trichlorosilane through a pressure equalizing dropping funnel under stirring, stirring and reacting for 30-45 minutes, separating an organic layer, adding anhydrous potassium carbonate and anhydrous calcium chloride to the organic matter, stirring at room temperature for 12-14 hours, filtering, and concentrating the filtered solution by rotary evaporation to obtain hydrogen silsesquioxane;
[0008] Furthermore, the proportion of each component in the preparation process of the hydrogen silsesquioxane includes, by mass fraction: 140-160 parts of ferric chloride, 200-240 parts of methanol, 100-105 parts of concentrated hydrochloric acid, 1750-2000 parts of petroleum ether, 250-300 parts of toluene, and 100-110 parts of trichlorosilane;
[0009] S2: Add hydrogen silsesquioxane and a magnetic bar into a reaction container, add toluene and allyl glycidyl ether in sequence after drying, stir evenly, add Karstedt catalyst, stir and react for 30-45 minutes, heat to 95°C and keep warm for 36-40 hours, remove the solvent and allyl glycidyl ether under reduced pressure to obtain glycidyl ether propyl POSS;
[0010] Furthermore, the proportion of each component in the preparation process of the glycidyl ether propyl POSS includes, by mass fraction: 1-1.5 parts of hydrogen silsesquioxane, 10-12 parts of toluene, 3-4 parts of allyl glycidyl ether, and 0.005-0.006 parts of Karstedt catalyst;
[0011] S3: Add glycidyl ether propyl POSS, perfluorononanoic acid, and tetrabutylammonium bromide to 1,4-dioxane, heat and reflux for reaction for 8-9 hours, cool to room temperature, remove the solvent by rotary evaporation, add the product to chloroform, stir evenly, separate the organic layer, wash the organic layer with 0.1M sodium bicarbonate solution, dry the organic layer with anhydrous magnesium sulfate, filter, remove the solvent by rotary evaporation, add the crude product to acetonitrile, stir evenly, filter, and dry in vacuo to obtain fluoroalkyl-modified glycidyl ether propyl POSS;
[0012] Furthermore, the proportion of each component in the preparation process of the fluoroalkyl-modified glycidyl ether propyl POSS includes, by mass fraction: 1-2 parts of glycidyl ether propyl POSS, 0.15-0.2 parts of perfluorononanoic acid, and 0.015-0.016 parts of tetrabutylammonium bromide;
[0013] S4: Add 3-mercaptopropyltrimethoxysilane and concentrated hydrochloric acid to methanol, heat to 90-92°C for reaction for 24 hours, wash the crude product with methanol, add the crude product to dichloromethane, stir evenly, wash with deionized water, separate the organic layer, dry the organic layer with anhydrous sodium sulfate, and concentrate by rotary evaporation to obtain mercaptopropyl POSS;
[0014] Furthermore, the proportion of each component in the preparation process of the mercaptopropyl POSS includes, by mass fraction: 15-20 parts of 3-mercaptopropyltrimethoxysilane, 30-35 parts of concentrated hydrochloric acid, and 360-400 parts of methanol;
[0015] S5: Add tridecafluorooctyl methacrylate and photoinitiator 907 to tetrahydrofuran, stir evenly to obtain solution A; add mercaptopropyl POSS to tetrahydrofuran, stir evenly to obtain solution B; under nitrogen atmosphere, add solution A to solution B, stir and react under ultraviolet light for 6-7 hours, filter, remove the solvent by rotary evaporation, add the product to anhydrous ethanol, centrifuge, wash with anhydrous ethanol, and vacuum dry at 50°C for 24-36 hours to obtain fluoroalkyl-modified mercaptopropyl POSS;
[0016] Furthermore, the proportion of each component in the preparation process of the fluoroalkyl-modified mercaptopropyl POSS includes, by mass fraction: 4.8-5.6 parts of tridecafluorooctyl methacrylate, 9070.05-0.06 parts of photoinitiator, and 2.69-2.88 parts of mercaptopropyl POSS;
[0017] S6: Hexanediol diacrylate and photoinitiator 907 are added to epoxy resin in sequence, and stirred evenly. The mixture is added to tetrahydrofuran and stirred evenly. Fluoroalkyl-modified mercapto POSS, PDMS-modified glycidyl ether propyl POSS, and ethanol are added in sequence, and ultrasonic dispersion is performed for 1 hour, and stirred evenly to obtain coating A.
[0018] Furthermore, the proportion of each component in the preparation process of the coating A includes, by mass, 8-16 parts of epoxy resin, 2-4 parts of hexanediol diacrylate, 0.02-0.04 parts of photoinitiator 907, 3.2-6.4 parts of fluoroalkyl-modified mercapto POSS, 0.5-1 parts of PDMS-modified glycidyl ether propyl POSS, 710-1420 parts of tetrahydrofuran, and 178-355 parts of ethanol;
[0019] Further, the amount of the fluoroalkyl-modified mercapto POSS added is 40-41% of the mass of the epoxy resin:
[0020] Furthermore, the amount of ethanol added is 25-26% of the mass of tetrahydrofuran;
[0021] Further, the PDMS modified glycidyl ether propyl POSS is prepared by reacting PDMS with an amino group at the end with an excess of glycidyl ether propyl POSS;
[0022] Further, the molecular weight of the PDMS with an amino group at the end includes 2000;
[0023] S7: adding glycidyl ether propyl POSS and fluoroalkyl modified glycidyl ether propyl POSS to butanone, stirring evenly, adding triaryl sulfonium hexafluoroantimonate mixture, stirring evenly, to obtain coating B;
[0024] Furthermore, the proportion of each component in the preparation process of the coating B includes, by mass, 8-10 parts of glycidyl ether propyl POSS, 0.52-0.64 parts of fluoroalkyl modified glycidyl ether propyl POSS, 0.28-0.35 parts of triaryl sulfonium hexafluoroantimonate mixture, and 200-240 parts of butanone;
[0025] S8: pre-treat the surface of the metal part for standby use;
[0026] S9: Spray coating A on the surface of the pretreated metal part, and UV-cure it for 5-6 minutes under a nitrogen atmosphere to form coating A; treat the surface of coating A with oxygen plasma for 5-6 minutes, spin-coat coating B on the surface of coating A, evaporate the solvent in a nitrogen atmosphere at 60-62°C, and UV-cure it for 10-30 minutes to obtain coating B, thereby obtaining a wear-resistant and corrosion-resistant metal part.
[0027] Furthermore, the specific operation steps of the coating A spraying process include a spray gun caliber of 1.0-1.1 mm, a tassel of 0.25-0.28 mL / s, a compressed air pressure of 0.6-0.62 MPa, a distance between the pre-treated metal surface and the spray gun mouth of 25-27 cm, an "S"-shaped spray during the spraying process, and a spray gun movement rate of 2.8-3 cm / s;
[0028] Furthermore, during the UV curing process of the coating A, the light source includes a 1000W high-pressure mercury lamp, and the distance between the surface of the metal part and the light source is 28-30cm;
[0029] Further, the thickness of the coating A is 8-12 μm;
[0030] Further, the concentration of coating B during the spin coating process is 4-5wt%;
[0031] Furthermore, during the UV curing process of the coating B, the light source includes a 500W mercury lamp, and the light source irradiates the surface of the coating A through a 300nm filter.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention controls the addition amount of fluoroalkyl-modified mercapto POSS and ethanol in coating A. Based on the characteristic that the volatility of tetrahydrofuran is greater than that of ethanol, when the tetrahydrofuran evaporates, the ethanol that is not completely evaporated in coating A can induce the fluoroalkyl-modified mercapto POSS to form relatively large particles. This characteristic is utilized to first form a rough hydrophobic coating with a micro-nano composite structure on the surface of the metal part. On the one hand, the fluoroalkyl group itself gives it the property of low surface energy. On the other hand, the well-arranged concave structure formed by the relatively large particles provides mechanical locking properties for coating B. Combined with the joint action of oxygen plasma, even super-hydrophobicity and low surface energy can make the coating have excellent firmness, which is different from the traditional surface roughness treatment of metal parts and retains the original gloss of the metal part surface.
[0034] 2. The present invention further controls the concentration of coating B so that it can be filled in the concave structure on the surface of coating A, but can still expose most of the micro-nano cluster structure of coating A, while maintaining the excellent hydrophobicity of the coating, enhancing the wear resistance of the coating. When the top of the micro-nano cluster of coating A is partially worn away, the coating B filled in the concave part of coating A is exposed, and the fluoroalkyl-modified glycidyl ether propyl POSS and glycidyl ether propyl POSS in coating B maintain the hydrophobicity of the coating, and the area of the hydrophobic region increases after friction, further ensuring the hydrophobicity of the coating, thereby achieving the purpose of enhancing the wear resistance of the coating. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the following examples, all materials were purchased from common commercial sources.
[0037] The preparation process of hydrogen silsesquioxane comprises the following steps: adding 140 parts of ferric chloride into 200 parts of methanol, stirring evenly, adding 100 parts of concentrated hydrochloric acid, 1750 parts of petroleum ether and 250 parts of toluene in sequence, stirring evenly, adding the evenly stirred mixture into 100 parts of petroleum ether solution of trichlorosilane through a pressure equalizing dropping funnel under stirring, stirring and reacting for 30 minutes, separating the organic layer, adding 50 parts of anhydrous potassium carbonate and 50 parts of anhydrous calcium chloride into the organic matter, stirring at room temperature for 12 hours, filtering, and concentrating the filtered solution by rotary evaporation to obtain hydrogen silsesquioxane.
[0038] The preparation process of glycidyl ether propyl POSS comprises the following steps: adding 1 part of hydrogen silsesquioxane and a magnetic bar into a reaction container, adding 10 parts of toluene and 3 parts of allyl glycidyl ether in sequence after drying, stirring evenly, adding 0.005 parts of Karstedt catalyst, stirring for reaction for 30 minutes, heating to 95°C and keeping the temperature for reaction for 36 hours, removing the solvent and allyl glycidyl ether under reduced pressure, and obtaining glycidyl ether propyl POSS.
[0039] The preparation process of mercaptopropyl POSS comprises the following steps: adding 15 parts of 3-mercaptopropyltrimethoxysilane and 30 parts of concentrated hydrochloric acid into methanol, heating to 90°C to react for 24 hours, washing the crude product with 360 parts of methanol, adding the crude product into 100 parts of dichloromethane, stirring evenly, washing with deionized water, separating the organic layer, drying the organic layer with anhydrous sodium sulfate, and concentrating by rotary evaporation to obtain mercaptopropyl POSS.
[0040] The preparation process of fluoroalkyl modified glycidyl ether propyl POSS comprises the following steps: adding 1 part of glycidyl ether propyl POSS, 0.15 parts of perfluorononanoic acid and 0.015 parts of tetrabutylammonium bromide to 5 parts of 1,4-dioxane, heating and refluxing for 8 hours, cooling to room temperature, removing the solvent by rotary evaporation, adding the product to chloroform, stirring evenly, separating the organic layer, washing the organic layer with 0.1M sodium bicarbonate solution, drying the organic layer with anhydrous magnesium sulfate, filtering, removing the solvent by rotary evaporation, adding the crude product to acetonitrile, stirring evenly, filtering and vacuum drying to obtain fluoroalkyl modified glycidyl ether propyl POSS.
[0041] The preparation process of fluoroalkyl modified mercaptopropyl POSS comprises the following steps: adding 4.8 parts of methacrylate tridecafluorooctyl ester and 0.05 parts of photoinitiator 907 into 10 parts of tetrahydrofuran, stirring evenly, and obtaining solution A; adding 2.69 parts of mercaptopropyl POSS into 10 parts of tetrahydrofuran, stirring evenly, and obtaining solution B; adding solution A into solution B under nitrogen atmosphere, stirring and reacting for 6 hours under ultraviolet light irradiation, filtering, removing the solvent by rotary evaporation, adding the product into anhydrous ethanol, centrifuging, washing with anhydrous ethanol, and vacuum drying at 50°C for 24 hours to obtain fluoroalkyl modified mercaptopropyl POSS.
[0042] Example 1: A surface treatment process for wear-resistant and corrosion-resistant metal parts: S1: 2 parts of hexanediol diacrylate and 0.02 parts of photoinitiator 907 are added to 8 parts of epoxy resin in sequence, and stirred evenly. The mixture is added to 710 parts of tetrahydrofuran and stirred evenly. 3.2 parts of fluoroalkyl-modified mercapto POSS, 0.5 parts of PDMS-modified glycidyl ether propyl POSS, and 178 parts of ethanol are added in sequence, ultrasonically dispersed, and stirred evenly to obtain coating A;
[0043] S2: 8 parts of glycidyl ether propyl POSS and 0.52 parts of fluoroalkyl modified glycidyl ether propyl POSS were added to 200 parts of butanone, and the mixture was stirred evenly. 0.28 parts of triarylsulfonium hexafluoroantimonate mixture was added and stirred evenly to obtain coating B;
[0044] S3: pre-treat the surface of the metal parts for standby use;
[0045] S4: Spray coating A on the surface of the pretreated metal part, and UV-curing for 5 minutes under a nitrogen atmosphere to form coating A; subject the surface of coating A to oxygen plasma treatment for 5 minutes, spin-coat coating B on the surface of coating A, evaporate the solvent in a nitrogen atmosphere at 60°C, and UV-curing for 10 minutes to obtain coating B, thereby obtaining a wear-resistant and corrosion-resistant metal part. The thickness of coating A is 8 μm; the concentration of coating B is 4.26 wt%.
[0046] Example 2: A surface treatment process for wear-resistant and corrosion-resistant metal parts: S1: 4 parts of hexanediol diacrylate and 0.04 parts of photoinitiator 907 are added to 16 parts of epoxy resin in sequence, and stirred evenly. The mixture is added to 1420 parts of tetrahydrofuran and stirred evenly. 6.4 parts of fluoroalkyl-modified mercapto POSS, 1 part of PDMS-modified glycidyl ether propyl POSS, and 355 parts of ethanol are added in sequence, ultrasonically dispersed, and stirred evenly to obtain coating A;
[0047] S2: 10 parts of glycidyl ether propyl POSS and 0.64 parts of fluoroalkyl modified glycidyl ether propyl POSS were added to 240 parts of butanone, and the mixture was stirred evenly. 0.35 parts of triarylsulfonium hexafluoroantimonate mixture was added and stirred evenly to obtain coating B;
[0048] S3: pre-treat the surface of the metal parts for standby use;
[0049] S4: Spray coating A on the surface of the pretreated metal part, and UV-curing for 5 minutes under a nitrogen atmosphere to form coating A; subject the surface of coating A to oxygen plasma treatment for 5 minutes, spin-coat coating B on the surface of coating A, evaporate the solvent in a nitrogen atmosphere at 60°C, and UV-curing for 10 minutes to obtain coating B, thereby obtaining a wear-resistant and corrosion-resistant metal part. Wherein, the thickness of coating A is 12 μm; the concentration of coating B is 4.43 wt%.
[0050] Comparative Example 1: A surface treatment process for wear-resistant and corrosion-resistant metal parts: S1: 2 parts of hexanediol diacrylate and 0.02 parts of photoinitiator 907 are added to 8 parts of epoxy resin in sequence, and stirred evenly. The mixture is added to 710 parts of tetrahydrofuran and stirred evenly. 2.4 parts of fluoroalkyl-modified mercapto POSS, 0.5 parts of PDMS-modified glycidyl ether propyl POSS, and 178 parts of ethanol are added in sequence, ultrasonically dispersed, and stirred evenly to obtain coating A;
[0051] The remaining steps are the same as those in Example 1.
[0052] Comparative Example 2: A surface treatment process for wear-resistant and corrosion-resistant metal parts: S1: 2 parts of hexanediol diacrylate and 0.02 parts of photoinitiator 907 are added to 8 parts of epoxy resin in sequence, and stirred evenly. The mixture is added to 710 parts of tetrahydrofuran and stirred evenly. 4 parts of fluoroalkyl-modified mercapto POSS, 0.5 parts of PDMS-modified glycidyl ether propyl POSS, and 178 parts of ethanol are added in sequence, ultrasonically dispersed, and stirred evenly to obtain coating A;
[0053] The remaining steps are the same as those in Example 1.
[0054] Comparative Example 3: A surface treatment process for wear-resistant and corrosion-resistant metal parts: S1: 2 parts of hexanediol diacrylate and 0.02 parts of photoinitiator 907 are added to 8 parts of epoxy resin in sequence, and stirred evenly. The mixture is added to 710 parts of tetrahydrofuran and stirred evenly. 3.2 parts of fluoroalkyl-modified mercapto POSS, 0.5 parts of PDMS-modified glycidyl ether propyl POSS, and 142 parts of ethanol are added in sequence, ultrasonically dispersed, and stirred evenly to obtain coating A;
[0055] The remaining steps are the same as those in Example 1.
[0056] Comparative Example 4: A surface treatment process for wear-resistant and corrosion-resistant metal parts: S1: 2 parts of hexanediol diacrylate and 0.02 parts of photoinitiator 907 are added to 8 parts of epoxy resin in sequence, and stirred evenly. The mixture is added to 710 parts of tetrahydrofuran and stirred evenly. 3.2 parts of fluoroalkyl-modified mercapto POSS, 0.5 parts of PDMS-modified glycidyl ether propyl POSS, and 213 parts of ethanol are added in sequence, ultrasonically dispersed, and stirred evenly to obtain coating A;
[0057] The remaining steps are the same as those in Example 1.
[0058] Comparative Example 5: A surface treatment process for wear-resistant and corrosion-resistant metal parts: S2: 6 parts of glycidyl ether propyl POSS and 0.39 parts of fluoroalkyl-modified glycidyl ether propyl POSS were added to 200 parts of butanone, and stirred evenly, and 0.28 parts of triarylsulfonium hexafluoroantimonate mixture were added, and stirred evenly to obtain coating B;
[0059] S3: pre-treat the surface of the metal parts for standby use;
[0060] S4: Spray coating A on the surface of the pretreated metal part, and UV-curing for 5 minutes under nitrogen atmosphere to form coating A; oxygen plasma treatment is performed on the surface of coating A for 5 minutes, and coating B is spin-coated on the surface of coating A, and the solvent is evaporated at 60°C under nitrogen atmosphere, and UV-curing is performed for 10 minutes to obtain coating B, thereby obtaining a wear-resistant and corrosion-resistant metal part. Among them, the thickness of coating A is 8μm; the concentration of coating B is 3.2wt%;
[0061] The remaining steps are the same as those in Example 1.
[0062] Comparative Example 6: A surface treatment process for wear-resistant and corrosion-resistant metal parts: S2: 12 parts of glycidyl ether propyl POSS and 0.78 parts of fluoroalkyl-modified glycidyl ether propyl POSS were added to 200 parts of butanone, and stirred evenly, and 0.28 parts of triarylsulfonium hexafluoroantimonate mixture were added, and stirred evenly to obtain coating B;
[0063] S3: pre-treat the surface of the metal parts for standby use;
[0064] S4: Spray coating A on the surface of the pretreated metal part, and UV-curing for 5 minutes under a nitrogen atmosphere to form coating A; subject the surface of coating A to oxygen plasma treatment for 5 minutes, spin-coat coating B on the surface of coating A, evaporate the solvent in a nitrogen atmosphere at 60°C, and UV-curing for 10 minutes to obtain coating B, thereby obtaining a wear-resistant and corrosion-resistant metal part. The thickness of coating A is 8 μm; the concentration of coating B is 6.39 wt%;
[0065] The remaining steps are the same as those in Example 1.
[0066] Experiment: Wear resistance test: The wear resistance of the wear-resistant and corrosion-resistant metal parts prepared in the above embodiments and comparative examples was tested using a wear tester. The friction head was an SDC standard friction cloth with a load of 100 g. After 300 reciprocating frictions, the contact angle of the wear-resistant and corrosion-resistant metal parts was measured.
[0067] Corrosion resistance test: The wear-resistant and corrosion-resistant metal parts prepared in the above embodiments and comparative examples were immersed in a hydrochloric acid solution with a pH of 1 and a sodium hydroxide solution with a pH of 14 for 24 hours. After being taken out and dried, the contact angles of the wear-resistant and corrosion-resistant metal parts were measured.
[0068] Light transmittance test: The coating A and coating B prepared in the above examples and comparative examples were used to prepare light transmittance test samples by the following method. The specific steps include: spraying coating A on the surface of a polycarbonate plate, UV curing for 5-6 minutes under a nitrogen atmosphere to form a coating A; treating the surface of coating A with oxygen plasma for 5-6 minutes, spin-coating coating B on the surface of coating A, evaporating the solvent in a nitrogen atmosphere at 60-62°C, UV curing for 10-30 minutes, and obtaining coating B, thereby obtaining a light transmittance test sample. Among them, the thickness of coating A is 8μm; the concentration of coating B is 4.26wt%. The light transmittance of the coating is tested by a UV spectrophotometer.
[0069] The specific test data is shown in Table 1 below.
[0070] Table 1 Wear and corrosion resistance metal parts performance test data table
[0071]
[0072] Conclusion: The wear-resistant and corrosion-resistant metal parts prepared by the surface treatment process of the present invention have excellent wear and corrosion resistance and can retain the metal's own luster.
[0073] In comparative example 1, the amount of fluoroalkyl-modified mercapto POSS is too little, the average surface roughness of coating A is reduced, the micron cluster structure is not obvious, the gap between the micron cluster structure is large, and the mechanical locking performance with coating B is reduced, resulting in reduced wear resistance.
[0074] In comparative example 2, the fluoroalkyl-modified mercapto POSS has an increased average surface roughness of coating A and a reduced gap between micron-cluster structures. During the spin coating of coating B with the same concentration, the smaller POSS in coating B easily fills and covers most of the micron-cluster structures of coating A, resulting in a decrease in the number of surface microstructures and a decrease in the contact angle. At the same time, due to the large-sized particles formed in coating A due to the ethanol-induced aggregation, the transmittance is reduced.
[0075] In comparative example 3, there is too little ethanol, and the microstructure formed by POSS in coating A during ethanol-induced aggregation is mainly nanoscale structure, which cannot hold up water droplets, resulting in a decrease in contact angle.
[0076] In comparative example 4, there was too much ethanol, and large particle structures were formed on the surface of coating A, and the number of surface microstructures was reduced, resulting in a decrease in the contact angle.
[0077] In comparative example 5, the concentration of coating B is too low, and the smaller hydrophobic POSS filled in the depressions of the microstructure on the surface of coating A is too far away from the top of the micron cluster structure formed by coating A. As a result, when the top of the micron cluster structure is partially worn away, the hydrophobic POSS in the depression cannot be exposed, and the area of the hydrophobic region after friction cannot be increased, resulting in reduced wear resistance.
[0078] In comparative example 6, the concentration of coating B is too high, resulting in the complete filling of the surface microstructure of coating A. The coating no longer presents a structure with a gradient refractive index. After spin coating, coating B forms a micrometer-level flat coating on the surface of coating A, resulting in a decrease in light transmittance.
[0079] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A surface treatment process for wear-resistant and corrosion-resistant metal parts, characterized in that: The following steps are involved: S1: Hexanediol diacrylate and photoinitiator 907 are added to epoxy resin in sequence, and stirred evenly. The mixture is added to tetrahydrofuran and stirred evenly. Fluoroalkyl-modified mercapto POSS, PDMS-modified glycidyl ether propyl POSS, and ethanol are added in sequence, and ultrasonic dispersion is performed and stirred evenly to obtain coating A; S2: adding glycidyl ether propyl POSS and fluoroalkyl modified glycidyl ether propyl POSS to butanone, stirring evenly, adding triaryl sulfonium hexafluoroantimonate mixture, stirring evenly, to obtain coating B; S3: pre-treat the surface of the metal parts for standby use; S4: spray coating A on the surface of the pretreated metal part, and UV-curing for 5-6 minutes under a nitrogen atmosphere to form coating A; The surface of coating A is treated with oxygen plasma for 5-6 minutes, coating B is spin-coated on the surface of coating A, the solvent is evaporated in a nitrogen atmosphere at 60-62°C, and UV-cured for 10-30 minutes to obtain coating B, thereby obtaining a wear-resistant and corrosion-resistant metal part; The metal surface pretreatment step includes grinding and degreasing. The grinding step includes grinding the surface of the metal part using a polishing machine, wherein the abrasive in the polishing machine includes any one of artificial corundum and artificial corundum, wherein the particle size of the artificial corundum includes 24-320 meshes, the particle size of the artificial corundum includes 24-280 meshes, the diameter of the grinding wheel during the grinding process includes 200-250 mm, and the rotation speed includes 1500-2400 rpm. The degreasing step includes immersing the ground metal part in acetone for degreasing.
2. The surface treatment process of a wear-resistant and corrosion-resistant metal part according to claim 1, characterized in that: The preparation process of the fluoroalkyl modified mercapto POSS comprises the following steps: adding tridecafluorooctyl methacrylate and photoinitiator 907 into tetrahydrofuran, stirring evenly to obtain solution A; adding mercaptopropyl POSS into tetrahydrofuran, stirring evenly to obtain solution B; adding solution A into solution B under nitrogen atmosphere, stirring and reacting for 6-7 hours under ultraviolet light irradiation, filtering, rotary evaporation, adding the product into anhydrous ethanol, centrifuging, washing, and vacuum drying to obtain the fluoroalkyl modified mercaptopropyl POSS.
3. The surface treatment process of a wear-resistant and corrosion-resistant metal part according to claim 2 is characterized in that: The proportions of various components in the preparation process of fluoroalkyl-modified mercaptopropyl POSS include, by mass fraction: 4.8-5.6 parts of tridecafluorooctyl methacrylate, 9070.05-0.06 parts of photoinitiator, and 2.69-2.88 parts of mercaptopropyl POSS.
4. The surface treatment process for wear-resistant and corrosion-resistant metal parts according to claim 1, characterized in that: The preparation method of the fluoroalkyl modified glycidyl ether propyl POSS comprises the following steps: adding glycidyl ether propyl POSS, perfluorononanoic acid and tetrabutylammonium bromide into 1,4-dioxane, heating and refluxing for reaction for 8-9 hours, cooling to room temperature, rotary evaporation, adding the product into chloroform, stirring evenly, separating the organic layer, washing, drying, filtering, rotary evaporation, adding the crude product into acetonitrile, stirring evenly, filtering and vacuum drying to obtain the fluoroalkyl modified glycidyl ether propyl POSS.
5. The surface treatment process for wear-resistant and corrosion-resistant metal parts according to claim 4 is characterized in that: The proportions of various components in the preparation process of fluoroalkyl-modified glycidyl ether propyl POSS include, by mass fraction: 1-2 parts of glycidyl ether propyl POSS, 0.15-0.2 parts of perfluorononanoic acid, and 0.015-0.016 parts of tetrabutylammonium bromide.
6. The surface treatment process for wear-resistant and corrosion-resistant metal parts according to claim 1, characterized in that: The proportions of each component in the preparation process of coating A, by mass, include: 8-16 parts of epoxy resin, 2-4 parts of hexanediol diacrylate, 0.02-0.04 parts of photoinitiator 907, 3.2-6.4 parts of fluoroalkyl-modified mercapto POSS, 0.5-1 parts of PDMS-modified glycidyl ether propyl POSS, 710-1420 parts of tetrahydrofuran, and 178-355 parts of ethanol.
7. The surface treatment process for wear-resistant and corrosion-resistant metal parts according to claim 1, characterized in that: The proportions of the components in the preparation process of coating B, by mass, include: 8-10 parts of glycidyl ether propyl POSS, 0.52-0.64 parts of fluoroalkyl modified glycidyl ether propyl POSS, 0.28-0.35 parts of triarylsulfonium hexafluoroantimonate mixture, and 200-240 parts of butanone.
8. The surface treatment process for wear-resistant and corrosion-resistant metal parts according to claim 1, characterized in that: The specific operating steps of the coating A spraying process include a spray gun caliber of 1.0-1.1mm, a tassel of 0.25-0.28mL / s, a compressed air pressure of 0.6-0.62MPa, a distance between the pre-treated metal part surface and the spray gun mouth of 25-27cm, an "S"-shaped spraying process, and a spray gun movement rate of 2.8-3cm / s; the light source during the UV curing process of the coating A includes a 1000W high-pressure mercury lamp, and the distance between the metal part surface and the light source is 28-30cm; the thickness of the coating A includes 8-12μm.
9. The surface treatment process for wear-resistant and corrosion-resistant metal parts according to claim 1, characterized in that: The concentration of coating B during the spin coating process is 4-5wt%; the light source during the UV curing of coating B includes a 500W mercury lamp, and the light source irradiates the surface of coating A through a 300nm filter.
10. A wear-resistant and corrosion-resistant metal part prepared by the surface treatment process of a wear-resistant and corrosion-resistant metal part according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lyophobic coating
CN105199457A
Super-wear-resisting super-hydrophobic coating and preparation method thereof
CN106398334A
Fluorine-containing monomer modified POSS (polyhedral oligomeric silsesquioxane)-based super-amphiphobic coating material as well as preparation method and application thereof
CN110130103A
High-strength wear-resistant aluminum alloy template and surface treatment process thereof
CN117534996A
High-strength corrosion-resistant aluminum-silicon glass and preparation method thereof
CN118791235A